Uji Potensi Ekstrak Cacing Laut Eunice siciliensis Terhadap Kadar Gula Darah Tikus Rattus novergicus - Nurfahmiatunnisa Nurfahmiatunnisa; Munif S Hassan; Andi Evi Erviani (Jurnal Ilmu Alam dan Lingkungan, 2019)
Diabetes is a disease associated with other diseases such as heart attacks and hypertension. Research has been conducted on "Test the Potential of Eunice Siciliensis Sea Worm Extract on Rattus Novergicus Rat Blood Sugar Levels". This study aims to determine the potential of Eunice Siciliensis Sea Worm Extract on the Blood Sugar Level of Rattus norvegicus Mice. In this study, dried sea worm extract was macerated, the maceration results will be evaporated after drying it. The test animal was induced with alloxan to increase blood sugar levels. Furthermore, treated with sea worm extract with doses of 45 6 gr/ kgdw, 90 6 gr/ kgdw and 180 6 gr/ kgdw, respectively. Positive control using acarbose, and negative control Na-cmc 1%. The results showed that administration of sea worm extract would reduce blood sugar levels in rats at a dose of 180 6 gr/ kgdw.